Рівень соціальної адаптації у дітей із синдромом Дауна залежно від здатності до вербальної комунікації - Сухонос, Оксана Сергіївна; Sukhonos, O. S. (My University, 2023)
Синдром Дауна, як і інші синдроми, асоційовані з психічною патологією, що виникає та розвивається у дитячому та/або підлітковому віці, часто перешкоджають нормальній адаптації особистості у соціумі. Діти із синдромом Дауна часто бувають тривожними, боязкими, неправильно розуміють наміри оточення, а тому неправильно їх тлумачать та реагують не належно; соціальні навички у таких дітей часто бувають недостатньо розвинені. Відірваність від оточення однолітків та соціальна ізоляція можуть зменшувати ефективність реабілітаційних програм для дітей із синдромом Дауна та поглиблювати когнітивний та афективний дефіцити у дітей із цим захворюванням. Мета дослідження — визначення рівня соціальної адаптації залежно від здатності до вербальної комунікації у дітей із синдромом Дауна. Дослідження проведено на базі КНП «Обласний медичний центр репродукції людини» ЗОР, де було обстежено 97 дітей із синдромом Дауна. Хворих було поділено на дві групи за критерієм спроможності до вербальної комунікації: до групи 1 (Г1) увійшли 77 дітей, здатних до вербальної комунікації, до групи 2 (Г2) — 20 дітей, які не розмовляють. Down syndrome, like other syndromes associated with mental pathology that occur and develop in childhood and/or adolescence, often prevent the normal adaptation of the individual in society. Children with Down syndrome are often anxious, timid, misunderstand the intentions of others, and therefore misinterpret them and react inappropriately; social skills in such children are often underdeveloped. Detachment from peers and social isolation can reduce the effectiveness of rehabilitation programs for children with Down syndrome and deepen cognitive and affective deficits in children with this disease. The aim of the study was to determine the level of social adaptation depending on the ability to verbal communication in children with Down syndrome. The research was carried out on the basis of the National Medical Center of ZOR, 97 children with Down's syndrome were thoroughly examined. The patients were divided into two groups according to the criterion of the ability to verbal communication: group 1 (G1) included 77 children capable of verbal communication, group 2 (G2) — 20 children who do not speak. As a result of the research, the level of social adaptation was determined depending on the ability to verbal communication in children with Down syndrome. Both in G1 and in G2, a normal level of adaptability, emotional comfort and manageability was revealed, which generally indicates a feeling of inner peace in a familiar environment and a high level of satisfaction with one's own microsocial environment. In G1 and G2, there was a decrease in the indicators of maladjustment, self-rejection, rejection of others, emotional discomfort, which can be interpreted as a decrease in the level of criticism of both oneself and others in both groups, regardless of the ability to speak. In G1, significantly higher levels of self-acceptance and internal control were found, which indicates higher self-esteem and the ability to independently solve difficult life situations in children with Down syndrome who are able to speak. In G2, a significant decrease in indicators of external control and escapism was established, which may be the result of a more gentle and careful attitude towards children with Down syndrome who are not capable of verbal communication.
Level of social adaptation in children with Down syndrome depending on verbal communication ability
Keywords: синдром Дауна; соціальна адаптація; соціальна тривожність; психокорекція; дитяча психіатрія; Down syndrome; social adaptation; social anxiety; psychocorrection; children psychiatry